Eco-literacy Training as Teaching Material for Surabaya Primary Teachers to Achieve SDGs - Susanti, Arik; Trisusana, Anis; Sueb; Asrori; Rosyid, Abdur (Jurnal Pena Indonesia, 2024)
The purpose of service activity is to describe how to create learning materials using various types of text by bringing eco-literacy approach and participants' responses. Our partners encounter a challenge wherein teachers struggle to provide instructional materials aligned with the concept of environmental awareness due to the continued emphasis on teacher-centred learning. The consequence is the students’ cognitive skills remain at a low level, and a lack of interest in environmental matters. Eco-literacy strategies are the solution to develop teachers’ instructional materials that align with the principles of sustainable development and environmental awareness and enhances stuents’ active learning. Workshops and socialization were implemented and 30 primary teachers in Surabaya participated. The instruments were a pre-post-test and a questionnaire. The results indicate that the teachers' comprehension of eco-literacy concept has been enhanced. They can also develop materials and lesson plan based on eco-literacy approach. In addition, nearly all teachers express feelings of enthusiasm and happiness regarding this activity, and 85% indicated they enable creating learning activities. It was concluded that this activity could improve their knowledge regarding the concept of eco-literacy. It is suggested to employ engaging instructional materials to facilitate the realization of SDGs.